PENGARUH PELATIHAN, KEJELASAN TUJUAN, DUKUNGAN ATASAN TERHADAP KEGUNAAN SISTEM AKUNTANSI KEUANGAN DAERAH DAN IMPLIKASINYA TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DAERAH (Studi Empiris Pada Pemerintah Kabupaten Lebak) - SUWIGNYO, DJOKO (JURNAL RISET AKUNTANSI TIRTAYASA, 2019)
ABSTRACTThis research is aimed to test the influence of training, goal clarity, supports of top leaders to the usefulness of regional financial accounting system. This research develops theoretical framework as basic hypothesis to answer research questions namely (1) There is influence of training on the usefulness of regional financial accounting system (2) There is influence of goal clarity to the usefulness of regional financial accounting system (3) There is influence of top leaders support to the usefulness of regional financial accounting system (4) There is influence of the usefulness of regional financial accounting system to the performance accountability of government institutions. The research population consists of 32 Local Government Agencies or SKPD in Lebak Regency. This research is quantitative study using survey method conducted to the SKPD’s in Lebak regency. The source of data used in this research is primary data. Primary data is data directly taken from respondents. Data analysis method to test hypothesis is Structural  Equation Modeling (SEM) analysis using Partial Least Square (PLS). The result of research shows that (1) Training influence positively and significantly to the usefulness of regional financial accounting system (2) Goal Clarity influence positively and significantly to the usefulness of regional financial accounting system (3) Top Leaders Supports influence positively and significantly to the usefulness of regional financial accounting system (4) The usefulness of regional financial accounting system influence positively and significantly  to the performance accountability of government institutions.Key words   :  Training, Goal Clarity, Top Leaders Support, usefulness of Regional Financial Accounting System, Its Implication on Performance Accountability